Access to 3-aminobenzothiophenes and 3-aminothiophenes fused to 5-membered heteroaromatic rings through 6π-electrocyclization reaction of keteniminium salts. Issue 34 (22nd August 2018) - Kolleth, Amandine; Müller, Simona; Lumbroso, Alexandre; Tanriver, Gamze; Catak, Saron; Sulzer-Mossé, Sarah; De Mesmaeker, Alain
Graphical abstract: Highlights: Keteniminium salts undergo facile 6π-electrocyclization reaction. A clear relation between the pKa of the amine and the formation of keteniminium salts has been established. Insight on the ease of this 6π-electrocyclization reaction was gained through competition reactions and DFT calculations. Abstract: We described a general approach to 3-aminobenzothiophenes and 3-aminothiophenes fused to 5-membered heteroaromatic rings as thiophenes, furans and pyrroles through a 6π-elctrocyclization reaction of keteniminium salts. We investigated various substituents not only on the aromatic rings, but also at C-2 and on the nitrogen atom of the keteniminium salt. In particular, we have determined the electronic requirements of the nitrogen substitution to secure the efficient formation of the corresponding keteniminium salt. A clear relation between the pKa of the amine leading to the formation of the keteniminium salt and the yield obtained for benzothiophene is established and should find broad application to other reactions involving these intermediates. Additional insight on the ease of this 6π-electrocyclization reaction was gained through competition reactions and DFT calculations.